2008
DOI: 10.3844/ajessp.2008.89.102
|View full text |Cite
|
Sign up to set email alerts
|

Use of Barley for the Purification of Aquaculture Wastewater in a Hydroponics System

Abstract: Barley was examined for its ability to remove nutrients from aquaculture wastewater. The effects of seed sterilization using ethanol and bleach and seed density on germination and plant growth were investigated. Surface sterilization of barley seeds had a negative impact on germination. Increasing the ethanol concentration and/or the bleach concentration reduced the germination percentage. Barley seeds were first germinated in water in the hydroponics system. The seedlings then received wastewater from an aqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Plant density can also cause nutrient limitations, although deficiencies ultimately depend on the ratio of plants to fish. In Snow and Ghaly (), seed quantity was not found to impact plant height. However, when the plant to fish ratio was increased in Endut et al .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Plant density can also cause nutrient limitations, although deficiencies ultimately depend on the ratio of plants to fish. In Snow and Ghaly (), seed quantity was not found to impact plant height. However, when the plant to fish ratio was increased in Endut et al .…”
Section: Discussionmentioning
confidence: 89%
“…Regardless of media type, treatments with plants had lower mean nitrate concentrations than the no-plant treatments (Table 1). Similarly, Snow and Ghaly (2008) produced barley hydroponically on aquaculture wastewater and found that the presence of barley resulted in significantly lower nitrate concentrations.…”
Section: Media Experimentsmentioning
confidence: 99%
“…Recent studies have indicated that nutrients from treated wastewater could be purified by using some plant species in a hydroponic system (Vaillant et al, 2004;Yang et al, 2008;Snow and Ghaly, 2008;Rababah and Ashbolt, 2000;Rababah and al-Shuha, 2009). Moreover, hydroponics (soilless) culture could lead to solve the global issues such as the shortage of water, environmental pollution, and instability of ecological system in various ways.…”
Section: Introductionmentioning
confidence: 99%
“…Each Petri dish contained ten seeds and was sealed with a strip of parafilm to prevent evaporation. Seeds were germinated in the dark for 7 days at room temperature (22°C) [30]. After 7 days number of leaves was counted, height of seedlings and length of roots were measured.…”
Section: Biologymentioning
confidence: 99%